The Role of Sugar in COVID Pandemic - Hilmi Sulaiman Rathomi (Faculty of Medicine, Public Health, and Nursing, 2021)
By the middle of August 2020, COVID-19 had infected over 20 million people worldwideand caused more than 700,000 deaths. The elderly and patients with comorbidities are themost affected group since they have a higher fatality rate because of COVID-19. For patientsyounger than fifty, the risk of death is just under one percent, but in the elderly, especiallythose over 65, the risk of death jumps 2 to 8 times 1,2 .The presence of comorbidities also significantly increases the risk of COVID-19 death.People with diabetes and obesity can increase their risk of death by 1.5 times, whilehypertension and heart disease raise the mortality up to 1.6 to 3 higher 3,4,5 . This situationshould make us aware; we are not only facing the COVID-19 pandemic but also a pandemicof non-communicable diseases (NCDs).There are so many people who are now suffering from obesity, diabetes, hypertension, andheart disease, they are the leading causes of worldwide deaths. Four main NCDs, i.e.cardiovascular diseases, cancer, diabetes, and chronic pulmonary diseases are responsible for82% of mortality 6 . One of the reasons that causes those diseases to have rapid growth, isbecause obesity, as the primary basis of almost all NCDs, is socially contagious 7 . Christakisexplained that people who have closeness with obese people, over time, will also be obese.Vice versa, obese people can cause people in their social circles to be obese for a certainperiod 8 .